Rod and slit photonic crystal microrings for on-chip cavity quantum electrodynamics - Lu Xiyuan; Zhou Feng; Sun Yi; Chanana Ashish; Wang Mingkang; McClung Andrew; Aksyuk Vladimir A.; Davanco Marcelo; Srinivasan Kartik (Nanophotonics)
Micro-/nanocavities that combine high quality factor (Q) and small mode volume (V) have been used to enhance light–matter interactions for cavity quantum electrodynamics (cQED). Whispering gallery mode (WGM) geometries such as microdisks and microrings support high-Q and are design- and fabrication-friendly, but V is often limited to tens of cubic wavelengths to avoid WGM radiation. The stronger modal confinement provided by either one-dimensional or two-dimensional photonic crystal defect geometries can yield sub-cubic-wavelength V, yet the requirements on precise design and dimensional control are typically much more stringent to ensure high-Q. Given their complementary features, there has been sustained interest in geometries that combine the advantages of WGM and photonic crystal cavities. Recently, a “microgear” photonic crystal ring (MPhCR) has shown promise in enabling additional defect localization (>$ > $10× reduction of V) of a WGM, while maintaining high-Q (≈106)$(≈ 1{0}^{6})$ and other WGM characteristics in ease of coupling and design. However, the unit cell geometry used is unlike traditional PhC cavities, and etched surfaces may be too close to embedded quantum nodes (quantum dots, atomic defect spins, etc.) for cQED applications. Here, we report two novel PhCR designs with “rod” and “slit” unit cells, whose geometries are more traditional and suitable for solid-state cQED. Both rod and slit PhCRs have high-Q (>106)$( > 1{0}^{6})$ with WGM coupling properties preserved. A further ≈10× reduction of V by defect localization is observed in rod PhCRs. Moreover, both fundamental and 2nd-order PhC modes co-exist in slit PhCRs with high Qs and good coupling. Our work showcases that high-Q/V PhCRs are in general straightforward to design and fabricate and are a promising platform to explore for cQED.